TINDAK TUTUR PENOLAKAN CINTA YANG DILAKUKAN OLEH PEREMPUAN DI KOTA SURAKARTA A PRAGMATIC STUDY: REFUSAL OF REQUEST - Muhammad Fatahillah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The development of the science is quickly spread in all branches of study. One of those studies is a language study. Linguistic is a study of language which are many studies are studied. Pragmatic is branch of Linguistic study that learns about study in meaning. Context is very important in pragmatic study; a language cannot only interpret by its structure but also by its context in order to get the meaning. Pragmatic also learns various studies; the research uses a pragmatic approach in order to analyze the data from the research in the form of refusal of request in speech act. The research is focused on the implementation refusal of request that happened in refusing of love by women. The study is using some theories from pragmatic expert such as Levinson (1983), Searle (1985) and Yule (1996;2022) with the aim to get understanding about speech act especially in refusals form. Furthermore, the strategies of refusal are divided into two part there are direct and indirect. Discourse completion task (DCT) is the method that used by the researcher to collect the data quickly and easily. The steps of collecting the data are the researcher firstly is distributing the questionnaires to 50 respondents’ women in range of age 18-25 years old in Surakarta City, secondly the researcher is analyzing the data, and lastly the researcher is presenting the data. The result of the research is the used of indirect refusal strategy is used a lot than direct strategy. The indirect strategy is founded by 39 data consists of 25 data indirect strategy with giving alternative and 14 data indirect strategy with giving reason. Whereas, the direct strategy is founded by 11 data consist of direct negative willingness with 6 data, direct performative with 4 data, and direct negative flat with one data. It concluded that the women respondents in Surakarta city more comfortable in conveying their rejection of love. Keywords: Pragmatic; Speech Act; Refusal of Requests